KETERAMPILAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN DI KELOMPOK B TAMAN KANAK-KANAK GEMBALA BAIK PONTIANAK - Ita Yolanda Sari; Marwawi R; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2021)
AbstractThe purpose of this research is to determine the teacher’s skills in use learning media in group B at TK Gembala Baik Pontianak.The teacher’s skills in question include; skills in choosing learning media, skills in varying the use of learning media, and skills in applying learning media. The subject in this research were five class B teachers, which taught classes B1, B2, B3, B4, and B5 at TK Gembala Baik Pontianak. The methods that used in this research is descriptive with a qualitative approach. Data collection in this research used interview, observation, and documentation techniques. The data in this research are results of interviews, the results of observations, and the result of documentation in the form of RPPH and photos of learning activities in 5 class of group B at TK Gembala Baik Pontianak. The results of this research show that the teacher’s skills in choosing learning media are categorized as good, the teacher’s skills in varying the use of learning media are categorized as good as enough, and the teacher’s skills in applying learning media are categorized as good.Keywords: Skills, Learning Media, Early Childhood Education Programs.